Barriers and facilitators in child and adolescent mental health services in a Middle Eastern country: qualitative study - Erna Judith Roach; Khalood Al-abri; Divya Kuzhivilayil Yesodharan; Judie Arulappan; Sulaiman Al Sabei; Muna Said Al Shekaili (BMC Health Services Research)
Abstract Objective The objective is to explore the barriers and facilitators experienced by mental health care professionals in providing mental health services to Omani children and adolescents. Methods A qualitative descriptive study with semi-structured face-to-face interviews was conducted on a purposive sample of sixteen mental health professionals from a tertiary care psychiatric hospital in Oman. Audio recordings were transcribed verbatim, and the anonymized transcripts were processed with Delve Tool, a qualitative data analysis software that streamlines thematic analysis. Results Barriers to access mental health services were- institutional system and policy limitations; specialized workforce deficiency; lack of systemic interagency coordination; logistical barriers, language barriers, resistance to treatment, inefficient facility design, and cultural stigma. Facilitators were - integrated team-based care; telemedicine and public awareness campaigns; existing expertise and integrated services model. Conclusion This study highlights the urgent need for action in ways to expand mental health education, and breakdown the stigma that often prevents people from seeking help. By integrating care models and ensuring that professionals receive ongoing training, the existing gaps can be closed and mental health services can be made more effective.